The efficacy of ampicillin and Lactobacillus casei rhamnosus in the active management of preterm premature rupture of membranes remote from term - Kavak, Salih Burcin (Dove Medical Press, 2014)
BACKGROUND: We aimed to investigate the treatment efficacy of ampicillin prophylaxis accompanied by Lactobacillus casei rhamnosus over the latency period following preterm premature rupture of membranes (PPROM). METHODS: Records of 40 patients who presented with PPROM between 23(0/7)–31(6/7) weeks were analyzed retrospectively. Patients were divided into two groups: group 1 (n=20), treated with ampicillin; and group 2 (n=20), treated with ampicillin plus L. casei rhamnosus. Clinical and laboratory parameters were compared. Delta (Δ) values of each laboratory parameter were calculated by subtracting the value at delivery from the values at admission to the clinic. RESULTS: Gestational weeks at delivery (28.1±0.3 weeks versus 31.5±0.4 weeks), latency periods (12.3±1.5 days versus 41.4±4.4 days), 5-minute APGAR scores (6.8±0.1 versus 7.8±0.1), and birth weights (1,320±98 g versus 1,947±128 g) were significantly higher in group 2. White blood cell (WBC) (12,820±353/mm(3) versus 11,107±298/mm(3)), and neutrophil counts (10.7±0.5×10(3)/L versus 8.2±0.5×10(3)/L) were significantly lower in group 2 at delivery. The ΔWBC (2,295±74/mm(3) versus −798±−406/mm(3)), ΔC-reactive protein (5±0.04 mg/L versus 1.6±0.2 mg/L), and Δneutrophil (3±0.2×10(3)/L versus 0.2±−0.1×10(3)/L) were significantly lower in group 2. CONCLUSION: It seems that addition of L. casei rhamnosus to ampicillin prolongs the latency period in patients with PPROM remote from term.